2017
DOI: 10.1016/j.physa.2016.11.127
|View full text |Cite
|
Sign up to set email alerts
|

Role of the hydrophobic and hydrophilic sites in the dynamic crossover of the protein-hydration water

Abstract: h i g h l i g h t s• The water diffusion near the protein surface is lower than in bulk.• A crossover in the diffusion of the hydration water is observed.• The crossover happens at different temperatures for hydrophilic and hydrophobic sites. g r a p h i c a l a b s t r a c t a b s t r a c t Molecular dynamics simulations were performed to study the water structure and dynamics in the hydration shell of the globular TS-Kappa protein. The results show that for a wide range of temperatures the diffusion coeffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 54 publications
(70 reference statements)
2
16
0
1
Order By: Relevance
“…On the basis of this approach, for what concerns the thermal limit of biological activity, the low-temperature threshold, TL225 K, corresponds to what was originally named the protein glass transition, below which the hydrogen-bonded network becomes too rigid to allow protein motions and the whole system can be considered in a glassy state. It corresponds to the temperature of the so-called water dynamical crossover at which point the population of local low-density water structures dominates over that of high-density local structures [27,35,52,53,60,64,65]. This change in the water density and in the corresponding dynamics of the hydrogen-bonded network triggers the amino acids motion and the protein activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of this approach, for what concerns the thermal limit of biological activity, the low-temperature threshold, TL225 K, corresponds to what was originally named the protein glass transition, below which the hydrogen-bonded network becomes too rigid to allow protein motions and the whole system can be considered in a glassy state. It corresponds to the temperature of the so-called water dynamical crossover at which point the population of local low-density water structures dominates over that of high-density local structures [27,35,52,53,60,64,65]. This change in the water density and in the corresponding dynamics of the hydrogen-bonded network triggers the amino acids motion and the protein activity.…”
Section: Resultsmentioning
confidence: 99%
“…Since the water monolayer covering the protein surface is essentially a bidimensional hydrogen-bonded network connecting the different water clusters and the hydrophilic moieties of the protein surface [22,23], the protein dynamics, and thus its function, is slave to water dynamics [24,25,26]. Hence, the magnitude of the self-diffusion of hydration water strictly influences the large-amplitude motion of protein residues that is needed for the corresponding functionality [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Water in the vicinity of hydrophobic and hydrophilic sites of the protein exhibits a dynamical behavior which is quite distinct when compared to bulk water. [20][21][22][23][24][25][26][27] Recently, experiments and simulations with water at the GFP and CYP proteins showed that water molecules at the biomolecule surface present a very slow dynamics and they get stuck in some places, suggesting the presence of fractal traps on the protein surface. 28,29 In these systems, the water near the protein exhibits a subdiffusive behavior in which the mean squared displacement (MSD) of the molecules grows nonlinearly with time, i.e., ⟨r 2 (t)⟩∝ t µ , in which µ < 1 for subdiffusion.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that the water dynamics and structure inside hydrophobic or hydrophilic pores can be quite distinct regarding the pore size [28][29][30] and even near hydrophobic or hydrophilic protein sites. 31 Three cations are considered: the standard monovalent sodium (Na + ), the divalent zinc (Zn 2+ ), and the trivalent iron (Fe 3+ ). The study of sodium removal is relevant due to its applications for water desalination.…”
Section: Introductionmentioning
confidence: 99%